Diagnosis of the breast tumors by Touch Cytology - سينو, سوزان; عدنان المعراوي ,; مهند نعساني,; صفاء الحلبي , (Latakia University Journal -Medical Sciences Series, 2022)
This study aimed to evaluate the efficiency of technology Touch Cytology in diagnosis breast cancer for 70 clinical cases that visited Aleppo private hospitals. The results indicated that there were 55 carcinoma cases, 36 of whom were diagnosed as Invasive Ductal Carcinoma, 51.4% of which were 8 Medullary Ductal Carcinoma, with a rate of 22.2. % and 19 cases of Invasive Lobular Carcinoma with a percentage of 27.1%, while the rest of the cases included 15 patients with a percentage of 21.5% who were classified as Benign tumors, and these results matched with the tissue sections embedded in paraffin histologically and computationally using Image J program. The clinical evaluation of the patients was followed up by Immunohistochemistry (Herb2neu, ER, PR), the sensitivity and specificity values ​​of Touch Cytology in the diagnosing were, respectively: 96.42%, 86.66%, and the Positive Predictive Value was 98.18%, while the Negative Predictive Value was 86.66%. This technology was able to determine the histological pattern in some cases by 35.7%, and the results of the statistical analysis showed significant differences between age, body mass index, blood groups and risk of breast cancer.